Рентгенологическое исследование подвижности скелета пояснично-крестцового отдела позвоночника некоторых млекопитающих - Пылыпчук, О.Я. (Вестник зоологии, 1975)
The article deals with the results of roentgenological study of the structure and expanse of movements in the lumbo-sacral region of mammals with different kind of support. The value of loin mobility as a whole and mobility distribution among the interior, middle and posterior regions of the loin are established, the dependence of this function on the animal mode of life and habit of motion is determined.